Traversing terra nullius: legal origins and Freudian fictions - P. Fitzpatrick (Law Text Culture, 1998)
The editorial prospectus for this volume opens with a concision which will not be emulated here: 'Terra Nullius is the principle of violence that inheres in every origin. And, in its wake, there is no law, no text, no culture, free of that violence'. In an immediate sense, this is an invitation to counter certain pacific pretensions of law. But we may also be editorially swayed towards a more pointed pursuit. That would involve tying law to the violence of the origin - not an origin whose violence has a fIxed and forceful palpability, but an origin which is pervaded by what is null or non-existent, and an origin whose violence is constantly impelled by that very nothingness. Such a scene of the origin is one I will now visit by way of an analytical retelling of an occidental myth of violent origination. This is one of the most influential myths of modernity, not so much in its gruesome immediacy as in its psychoanalytic attenuations.